Enrollment patterns among medicaid beneficiaries with sickle cell disease: Multistate findings from the sickle cell data collection program - Ashima Singh; Mahua Dasgupta; Hannah K. Peng; Mei Zhou; Catie Clyde; Brandon K. Attell; Jhaqueline Valle; Sarah L. Reeves; Jeffrey Huebner; Angela B. Snyder (PLoS ONE, 2025)
Background Majority of individuals living with sickle cell disease (SCD) in the United States are enrolled in Medicaid. The objective of the study was to determine the patterns of Medicaid enrollment among individuals with SCD. Method We determined the enrollment pattern among SCD Medicaid beneficiaries categorizing them in three groups: continuously enrolled, had exit and no return, had gaps in duration of enrollment during 2017–2019, leveraging the data from the Sickle Cell Data Collection Program in four states. We compared characteristics of individuals with gaps and those continuously enrolled using chi square tests. Results Among 5883 children and 9260 adults, 70.5% and 61.8% respectively, were continuously enrolled. Gaps were observed in 12.5% of children and 12.9% of adults. A significantly smaller proportion of adults with gaps as compared to those who had continuous enrollment were disabled (CA:30.6% vs 65.3%; GA:23.7% vs 77.6%; MI:40.1% vs 69.5%; WI:39.8% vs 77.0%). Of all observed gaps, 60% were among adults. Enrollment patterns and gap duration varied by state. Conclusion Approximately 12% of individuals with SCD have gaps in enrollment during our 3-year study period. Individuals with disabilities were more likely to have continuous enrollment. Future work is needed to determine reasons for observed gaps and their impact on SCD health outcomes.